2013
DOI: 10.1016/j.aap.2013.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Short and long sleep duration and risk of drowsy driving and the role of subjective sleep insufficiency

Abstract: Experimental sleep restriction increases sleepiness and impairs driving performance. However, it is unclear whether short sleep duration in the general population is associated with drowsy driving. The goal of the present study was to evaluate whether individuals in the general population who obtained sleep of 6 hours or less are more likely to report drowsy driving, and evaluate the role of perceived sleep sufficiency. Data exploring whether subgroups of short sleepers (those who report the most or least unme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 16 publications
2
48
0
Order By: Relevance
“…In Singapore, Yeo et al has reported that the prevalence of insomnia was 15.3 % in 1996 [5]. Sleep impairment is associated with an increased risk of hypertension, obesity, depression and cardiovascular diseases [6,7] and affects daily activities such as driving [8] and work [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Singapore, Yeo et al has reported that the prevalence of insomnia was 15.3 % in 1996 [5]. Sleep impairment is associated with an increased risk of hypertension, obesity, depression and cardiovascular diseases [6,7] and affects daily activities such as driving [8] and work [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is vital to human health, necessary for life, 1,2 and it serves critical roles in brain functions including neurobehavioral, cognitive and safety-related performance, [3][4][5][6][7][8][9][10][11][12][13] memory consolidation, 14,15 mood regulation, 16,17 nociception 18,19 and clearance of brain metabolites. 20,21 Sleep is also critically involved in systemic physiology, including metabolism, [22][23][24][25][26] appetite regulation, 27,28 immune and hormone function, [29][30][31][32][33] and cardiovascular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, when analyses were restricted to only those who report 0 nights/week of insufficient sleep, significant differences remained. Compared to those reporting 7-8 h of sleep, those who reported less than 5 or 6 h were more than 2.5 times as likely to report nodding off at the wheel [79]. Although other research suggests that short sleepers may not be at higher risk for driving accidents [78], the above findings suggest that some cognitive impairments may exist due to inability to maintain vigilance.…”
Section: Neurobehavioral Performancementioning
confidence: 94%
“…Several papers have shown that accidents are related to sleepiness caused by sleep apnea [69,72,73] and prolonged wakefulness [71,74,75]. Some evidence also suggests that short sleepers may exhibit more sleepiness than average [76,77], but currently there are very limited data to support the claim that short sleepers are more likely to experience auto accidents [78], though some evidence exists [79].…”
Section: Neurobehavioral Performancementioning
confidence: 98%